Acciones entrelazadas contra daños ambientales graves: el impacto de Shell en Nigeria - Pigrau, Antoni (2013)
The demand for natural resources and energy continues to growin the developed world and, with it, the negative impacts on the environment and the rights of the peoples directly affected by extractive activities undertaken by the largest transnational corporations. Three factors compel victims of serious environmental damage to resort simultaneously to any available avenue of legal action (whether judicial or non-judicial, national or international): (1) the link between environmental damage and human rights abuses; (2) weak legislation, combined with the inability or unwillingness of the law-enforcing institutions in many countries where such extractive activities take place; and (3) the absence of international avenues to claim direct liability from corporations. We call this phenomenon intertwined actions, as the various judicial actions undertaken by the victims end up mutually reinforcing and increasing the visibility of the problem. The aim of this paper is to show this reality on the basis of the various instances of litigation that are taking place in the specific context of Shell’s activities in the Niger delta.